2021
DOI: 10.4269/ajtmh.20-0783
|View full text |Cite
|
Sign up to set email alerts
|

Continued Outbreak of Ceftriaxone-Resistant Salmonella enterica Serotype Typhi across Pakistan and Assessment of Knowledge and Practices among Healthcare Workers

Abstract: Pakistan is experiencing the first known outbreak of extensively drug-resistant (XDR) Salmonella enterica serotype Typhi (resistant to third-generation cephalosporins). The outbreak originated in Hyderabad in 2016 and spread throughout the Sindh Province. Whereas focus has remained on Sindh, the burden of XDR typhoid in Punjab, the most populous province, and the rest of the country is understudied. Using laboratory data from Shaukat Khanum Memorial Cancer Hospital and Research Centre in Lahore (Punjab Provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…Third-generation cephalosporins (extended spectrum β-lactams) are frequently used in the treatment of typhoid fever. The emergence and spread of extensively drug-resistant (XDR) S. enterica Typhi in Pakistan, and now globally, is a publichealth concern as it has left azithromycin (one of the last oral antibiotics available) and meropenem (carbapenem) as the only options available for treatment [2][3][4][5][6][7][8] (https://emergency.cdc.gov/han/2021/han00439.asp).…”
Section: Introductionmentioning
confidence: 99%
“…Third-generation cephalosporins (extended spectrum β-lactams) are frequently used in the treatment of typhoid fever. The emergence and spread of extensively drug-resistant (XDR) S. enterica Typhi in Pakistan, and now globally, is a publichealth concern as it has left azithromycin (one of the last oral antibiotics available) and meropenem (carbapenem) as the only options available for treatment [2][3][4][5][6][7][8] (https://emergency.cdc.gov/han/2021/han00439.asp).…”
Section: Introductionmentioning
confidence: 99%
“…4 The XDR typhoid outbreak in Pakistan was first observed in the Sindh Province in 2016, with infections clustered around sewage lines in the city of Hyderabad. 10 Previously, we observed 2 an increase in XDR typhoid cases in the Punjab Province of Pakistan, with children bearing the greatest burden. This indicated that XDR typhoid had spread beyond the southern Sindh Province.…”
Section: Introductionmentioning
confidence: 92%
“…Recent and continued outbreaks of multidrug resistant (MDR) and extensively drug resistant (XDR) typhoid demonstrate the difficulty in containing this infectious disease. [1][2][3] According to the WHO, MDR S. Typhi are defined as resistant to the first-line recommended drugs for treatment, which include chloramphenicol, ampicillin, and trimethoprim-sulfamethoxazole. 4 XDR S. Typhi are defined as resistant to all recommended antibiotics for typhoid fever, which include third-generation cephalosporins and fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…There were 68 reported cases of imported ESBL Salmonella Typhi and Salmonella Paratyphi in the UK between 2017 and 2020 [ 56 ▪ ]. The majority of cases were associated with travel to Pakistan, where there is an ongoing outbreak of extremely drug-resistant S. Typhi in the Sindh province [ 57 , 58 ]. A separate multisite study of travelers with enteric fever found that 65% of S. Typhi isolates were resistant to multiple classes of antimicrobials [ 50 ▪▪ ].…”
Section: Enteric Fever In International Travelersmentioning
confidence: 99%